2013
DOI: 10.1590/s0034-72802013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravitreal bevacizumab or triamcinolone acetonide as a preoperative adjunct to vitrectomy for vitreous haemorrhage in diabetics

Abstract: The authors declare no conflicts of interest ABSTRACT Purpose: To evaluate the effect of preoperative intravitreal bevacizumab (IVB)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Nowadays, TA is the most used substance for vitreous identification and the currently technique application consists of a simple injection of the agent into the vitreous cavity ( figure 11). Following the initial report, a number of studies confirmed the efficacy of TA for staining the transparent vitreous, whereas anatomic or functional signs of complications have rarely been observed (4,8,68) . In addition to its effect on the vitreous visualization, a TA injection during vitrectomy may prevent fibrin reaction and post-operative PVR; however, there is no conclusive data about this possible effect.…”
Section: Triancinolone Acetonidementioning
confidence: 97%
“…Nowadays, TA is the most used substance for vitreous identification and the currently technique application consists of a simple injection of the agent into the vitreous cavity ( figure 11). Following the initial report, a number of studies confirmed the efficacy of TA for staining the transparent vitreous, whereas anatomic or functional signs of complications have rarely been observed (4,8,68) . In addition to its effect on the vitreous visualization, a TA injection during vitrectomy may prevent fibrin reaction and post-operative PVR; however, there is no conclusive data about this possible effect.…”
Section: Triancinolone Acetonidementioning
confidence: 97%
“…Dear Editor, We have read with great enthusiasm the recently published article entitled ''Use of intravitreal bevacizumab or triamcinolone acetonide as a preoperative adjunct to vitrectomy for vitreous haemorrhage in diabetics" by Ferraz et al 1 . We congratulate the authors for their lightening study.…”
mentioning
confidence: 99%
“…Em um estudo prospectivo de série de casos, a ação do BVZ como tratamento adjuvante com a PFC foi analisada nos olhos afetados com HV secundária a RDP (98) . No protocolo do estudo, a primeira injeção intravítrea (101) .…”
Section: Bvz E Rdpunclassified